2017
DOI: 10.3390/molecules22101642
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: Sulfonamides

Abstract: The sulfonamides and their structurally related derivatives, such as the sulfamates and sulfamides, possess the general formula A-SO2NHR, in which the functional group is either directly bound to an aromatic, heterocyclic, aliphatic, or sugar scaffold (of type A), or appended to such a scaffold via a heteroatom, most frequently oxygen or nitrogen (leading thus to sulfamates and sulfamides, respectively) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 47 publications
1
58
0
2
Order By: Relevance
“…Sulfonamides constitute an important class of drugs containing many types of pharmacological agents with broad-spectrum bacteriostatic activity. Sulfonamides interrupt the synthesis of folic acid, interfering with the dihydropteroate synthase and dihydrofolate reductase enzymes of bacteria (and protozoa) and inhibiting bacterial growth [179,180]. The sulfadoxine-pyrimethamine combination is used in some settings for the treatment of uncomplicated malaria in pregnant women, and it is the only drug currently recommended for intermittent preventive therapy during pregnancy [181].…”
Section: Sulfonamidesmentioning
confidence: 99%
“…Sulfonamides constitute an important class of drugs containing many types of pharmacological agents with broad-spectrum bacteriostatic activity. Sulfonamides interrupt the synthesis of folic acid, interfering with the dihydropteroate synthase and dihydrofolate reductase enzymes of bacteria (and protozoa) and inhibiting bacterial growth [179,180]. The sulfadoxine-pyrimethamine combination is used in some settings for the treatment of uncomplicated malaria in pregnant women, and it is the only drug currently recommended for intermittent preventive therapy during pregnancy [181].…”
Section: Sulfonamidesmentioning
confidence: 99%
“…An important pharmacophore group is a sulfonamide moiety characteristic for many chemical compounds used in medicine. Its importance stems from diverse biological activities such as antibacterial, anti-malarial, hypotensive, diuretic, hypoglycemic, anti-thyroid, anti-parasitic, anti-inflammatory, and anti-glaucomatous activity [5,22]. Furthermore, many studies from various scientific centers have shown that sulfonamides may exhibit an antitumor effect.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamides constitute an important family of drugs that have been extensively applied in human and veterinary medicine due to their general stability, bioavailability, and ease of preparation. 1 The compounds of this class (Fig. 1) have been clinically in use for decades, and some of which showed potent antitumor activity.…”
mentioning
confidence: 99%